Reproductive Biology and Technology in Animals - Carlos Gardón Poggi, Juan; Satué Ambrojo, Katy (Veterinary Medicine and Science, 2020)
Reproductive success is a very important objective to ensure the evolution of animal species. In this sense, interesting research has been carried out to clarify various aspects of reproduction in different animal species. In this way, recent advances in the knowledge of reproductive biology and biotechnology developed for both males and females have been key to improving efficiency in different aspects. Thus, advances in the knowledge of sperm handling, oocyte characteristics, different genomic aspects related to somatic cell nuclear transfer, and the reproductive microarchitecture system in sheep, cows, pigs, and other invertebrates such as gastropods and fish are presented in this book. Additionally, we also present the most relevant topics of each area, making a detailed review of the knowledge reported to date.